Dynamic plant-derived polysaccharide-based hydrogels. (1st March 2020) - Heidarian, Pejman; Kouzani, Abbas Z.; Kaynak, Akif; Paulino, Mariana; Nasri-Nasrabadi, Bijan; Zolfagharian, Ali; Varley, Russell
Highlights: Review on the fabrication processes of dynamic plant-derived hydrogels. Description of the properties of dynamic plant-derived hydrogels. Analysis of self-healing and self-recovery of dynamic plant-derived hydrogels. Discussions on the applications, challenges, and perspectives of these hydrogels. Abstract: Plant-derived polysaccharides are widely used to fabricate hydrogels because of their ease of gelation and functionalization, plus exceptional biological properties. As an example, nanocellulose is a suitable candidate to fabricate hydrogels for tissue engineering applications due to its enhanced mechanical and biological properties. However, hydrogels are prone to permanent failure whilst under load without the ability to reform their networks once damaged. Recently, considerable efforts are being made to fabricate dynamic hydrogels via installation of reversible crosslinks within their networks. In this paper, we review the developments in the design of dynamic hydrogels from plant-derived polysaccharides, and discuss their applications in tissue engineering, sensors, bioelectronics devices, etc. The main goal of the paper is to elucidate how the network design of hydrogels can influence their dynamic properties: self-healing and self-recovery. Complementary to this, current challenges and prospects of dynamic plant-derived hydrogels are discussed.